THU0182 Dyslipoproteinemia and its relation with the activity of the disease and its treatment in a large spanish multicentric lupus cohort. (23rd January 2014) - Pego-Reigosa, J.; Rúa, I.; Mouriño, C.; Galindo, M.; Lόpez-Longo, F.; Calvo, J.; García-Yébenes, M.; Tomero, E.; Uriarte, E.; Fito, C.; Sánchez, A.; Olivé, A.; et al.
Abstract : Background: Abnormalities in the lipid profile contribute to the increased risk of early atherosclerosis in patients with SLE Objectives: To study the dyslipoproteinemia in SLE and the influence of the disease activity and treatments on it. Patients: SLE patients from the RELESSER Registry with an active follow up in a Rheumatology Department. Variables: a) lipid profile: total, LDL/HDL cholesterol, triglycerides and atherogenic index (total/HDL cholesterol), b) SLE activity: SELENA-SLEDAI score, C3, C4 and anti-dsDNA antibodies and c) ongoing treatments. Dyslipoproteinemia is defined as the presence of at least one of the following criteria: total cholesterol ≥240mg/dl, triglycerides ≥180mg/dl or statins use. Methods . Retrospective study of the data collected at the moment of the last evaluation of the patient. We calculate the prevalence of dyslipoproteinemia and the correlations between lipid profile and the SLE activity and treatments. Results: 583 patients were included (88.3% females, mean age: 45 years, SLE duration: median 111 months). Table 1 shows the results of the analysis of lipid profile. The median of the SLEDAI score was 2 (IR: 0-4). 39.4% of the patients had a SLEDAI score =0. The SLE activity was mild (SLEDAI =1-4 points), moderate (5-9 points) and severe (≥10 points) in 43.4, 13.2 and 3.9% of the patients, respectively. Total cholesterol levels were significantly higher in the subgroup of patients with severe activity (p=0.009). The LDL cholesterol and the atherogenic index also were higher in that subgroup (p = n.s.). We did not find significant differences in the values of the lipid profile in the subgroup of patients with hypocomplementemia or positive anti-dsDNA antibodies. The percentage of patients on statin therapy was significantly higher in the group of patients with severe lupus activity (p=0.05). The patients on current treatment with corticosteroids or with 2 immunosupressors had a higher prevalence of dyslipoproteinemia than those without corticosteroids or with ≤1 immunosupresor (p=0.009 and p=0.04, respectively). Patients on antimalarial therapy had lower triglycerides levels and lower prevalence of dysliproteinemia than those without that treatment (p close to 0.05). Conclusions: One third of the Spanish SLE patients had dyslipoproteinemia. Total cholesterol levels and statin requirement are significantly higher in the patients with higher disease activity. The use of corticosteroids and a more aggressive immunosupressive regimen are associated with higher prevalence of dyslipoproteinemia. Disclosure of Interest: None Declared